Prevalence of Root Caries among patients visiting a Private Dental Hospital- A Retrospective study - FAREEN, H.FIRDUS; KUMAR.R, PRADEEP; SRI.RENGALAKSHMI, (The journal of contemporary issues in business and government, 2021)
Dental root caries have received a great deal of attention in the last few years. It can occur as a Primary or Secondary lesion and diagnosis, access and treatment are different than coronal caries. Early detection of root caries may help in tooth retention for longer years. But, there have been too few studies to define it’s natural history, it’s distribution in a population and associated factors. Thus, The aim of the study was to evaluate the prevalence of root caries and their associated factors among patients visiting private dental college. The clinical records of 1911 patients with root caries were evaluated. Date of age, gender, tooth with root caries were obtained from the records of the dental hospitals. The data was analysed using SPSS software. Chi Square Test was performed to compare two proportions. The analysis was done for: age, gender, tooth with root caries in this study. The overall prevalence rate of root caries was found to be 57.9% among males and 42.1% among females. The Prevalence increased for both sexes almost consistently with age. The mean age group of occurance of root caries was found to be 51-65 years (39.1%).The intra oral distribution pattern of root caries revealed that the most frequently affected tooth type was found to be maxillary first and second molar (19.7%) in maxillary arch. The least frequently affected tooth was the mandibular incisor (1.1%). The results of the study shows that the occurrence of root caries increases with increase in age. Hence, older adults deserve attention concerning their actual role in the epidemiology of principal oral diseases and require future caries prevention programs.